The Impact of Financial Literacy, Financial Technology, and Financial Inclusion on the Financial Performance of Micro, Small, and Medium Enterprises (MSMEs) in the Culinary Sector in Medan - Herti Kristiyani Silalahi; Rafida Khairani; Chorin Tandean; Tiffany Tanady; Andrian Andrian; Nasib Nasib (Yayasan Riset dan Pengembangan Intelektual, 2023)
This objective of this study to analyze and evaluate the impact of financial literacy, technology, inclusion, and performance on micro, small, and medium companies (MSMEs) in the culinary sector in Medan. MSME participants in the culinary industry must have a solid understanding of financial literacy, inclusivity, and expertise in financial technology. By equipping MSMEs with comprehensive knowledge of funding options and the requisite skills to make well-informed decisions in their pursuit of finance, this initiative will enhance their capacity to maintain their enterprises. Financial success may be influenced by several factors, including financial literacy, technology, and inclusion. Financial literacy encompasses the knowledge and confidence necessary to make well-informed decisions on personal finances. Financial technology, often known as fintech, refers to a type of financial service that greatly improves the effectiveness and efficiency of financial services. Financial inclusion encompasses the comprehensive and unimpeded participation and accessibility of people and collectives in the financial system. This study utilized quantitative research approaches and employed a sample size of 60 persons picked by simple random selection. The data analysis approach utilizes several linear regressions. The data suggested that there was a partial or simultaneous influence of financial literacy, technology, and inclusion on financial performance.